Comparative Genomics of Three Colletotrichum scovillei Strains and Genetic Analysis Revealed Genes Involved in Fungal Growth and Virulence on Chili Pepper - Hsieh, Dai-Keng; Chuang, Shu-Cheng; Chen, Chun-Yi; Chao, Ya-Ting; Lu, Mei-Yeh Jade; Lee, Miin-Huey; Shih, Ming-Che (Frontiers in Microbiology, 2022)
Colletotrichum scovillei causes anthracnose of chili pepper in many countries. Three strains of this pathogen, Coll-524, Coll-153 and Coll-365, show varied virulence on chili pepper. Among the three strains, Coll-365 showed significant defects in growth and virulence. To decipher the genetic variations among these strains and identify genes contributing to growth and virulence, comparative genomic analysis and gene transformation to show gene function were applied in this study. Compared to Coll-524, Coll-153 and Coll-365 had numerous gene losses including 32 candidate effector genes that are mainly exist in acutatum species complex. A cluster of 14 genes in a 34-kb genomic fragment was lost in Coll-365. Through gene transformation, three genes in the 34-kb fragment were identified to have functions in growth and/or virulence of C. scovillei. CsPLAA encoding a phospholipase A2-activating protein enhanced the growth of Coll-365. A combination of CsPLAA with one transcription factor CsBZTF and one C6 zinc finger domain-containing protein CsCZCP was found to enhance the pathogenicity of Coll-365. Introduction of CsGIP, which encodes a hypothetical protein, into Coll-365 caused a reduction in the germination rate of Coll-365. In conclusion, the highest virulent strain Coll-524 had more genes and encoded more pathogenicity related proteins and transposable elements than the other two strains, which may contribute to the high virulence of Coll-524. In addition, the absence of the 34-kb fragment plays a critical role in the defects of growth and virulence of strain Coll-365.